Association of income relative deprivation and sleep duration in China - Peng, Zijian; Wu, Lin (Frontiers in Psychology, 2022)
In recent years, the rapid development of China's economy has brought about a serious polarization between rich and poor, which makes people have to bear the impact of social changes on their physical and mental health while enjoying the benefits of social development. It is difficult to maintain normal sleep duration (7-9 hours), which has gradually become a social phenomenon. Based on the China Family Panel Studies(CFPS2018), this study explored the relationship between relative income deprivation and sleep duration at the micro level. This paper empirically tests that the probability of normal sleep duration(7-9 hours) decreases by 22.8% for each unit of income relative deprivation. This conclusion is significant at 0.05 level. On this basis, the instrumental variable method is used to overcome the endogenous problem, and a more accurate conclusion is obtained. After the robustness test and heterogeneity analysis of the model, a mediation model is constructed through Mplus: relative income deprivation - social trust - sleep duration. Social trust is considered as a mediation variable. This study believes that in Chinese society, the relative deprivation of individual income will affect their sleep duration by changing their social trust. Therefore, increasing the income of low-income groups, narrowing the gap between rich and poor, alleviating social conflicts and promoting interpersonal trust are important means to ensure that social members can have normal sleep duration.